Parenting styles and externalizing problem behaviors of preschoolers: mediation through self-control abilities and emotional management skills - WenLi, Zhang; Tiemei, Xu; Shuangqi, Li; Qun, Yu; Jingbo, Zhu; Sijie, Sun (Frontiers in Psychology, 2025)
IntroductionThe detection rate of externalizing problem behaviors among Chinese children has been increasing year by year. Before the age of six, the problem behaviors that appear in children are predominantly externalizing problem behaviors. Family is the starting point for children's socialization. Although some studies have explored the impact of parenting styles on children's externalizing problem behaviors, only a few have explored the underlying mechanisms driving this relationship.MethodsThis study attempts to fill this gap by investigating how self-control abilities and emotional management skills mediate the relationship between parenting styles and preschoolers' externalizing problem behaviors. Here, teachers and parents of 799 preschoolers from China were surveyed.ResultsThe findings of this investigation are 3-fold: (1) a significant association exists between the parenting styles adopted by parents and externalizing problem behaviors observed among preschoolers; (2) self-control abilities and emotional management skills independently mediate the associations between parenting styles and children's externalizing problem behaviors, highlighting their roles as mediators; and (3) sequential mediation of self-control abilities and emotional management skills elucidates a pathway through which parenting styles impact preschoolers' externalizing problem behaviors.DiscussionThis study clarified the relationship between parenting styles, externalizing problem behaviors of preschoolers, self-control abilities, and emotional management skills to provide a theoretical basis for solving the externalizing problem behaviors of preschoolers.